Quality of Pumpkin Fruits in Different Soil Managements - Amorim, Aiala Vieira; Lima Rocha, Raimundo Gleidison; Silva Paz, José Abel Aguiar da; Andrade, Francisca Aline da Silva; Moura, Carlos Farley Herbster; Costa, Rafael Santiago da; Oliveira, Letícia Kenia Bessa de; Barbosa, Francisca Edineide Lima; Araújo, Beatriz de Abreu; Nascimento Fernandes, Mirian Raquel do (International Journal of Advanced Engineering Research and Science, 2022)
To mitigate the effects of conventional agriculture, aiming at the sustainability of the ecosystem, it is necessary to use techniques that preserve the environment, reconciling food production with the reduction of environmental impacts in a sustainable way. In this sense, carrying out the cultivation keeping the native forest can be an alternative for maintaining sustainability in agricultural systems. Therefore, the objective of this work was to evaluate the postharvest quality of three pumpkin varieties (Cucurbita moschata) submitted to different soil management, aiming to obtain subsidies for the establishment of a promising management of this vegetable under field conditions. The study was carried out in an area located in the municipality of Acarape, Ceará, where two cultivation systems and three pumpkin cultivars were used, distributed in a split-plot scheme. Longitudinal (DL), transversal (DT), internal cavity (DCI), pulp firmness (FP), peel (CE) and pulp (EP) thicknesses were evaluated. The environmental factor influenced the longitudinal diameter and firmness of the pulp. Furthermore, higher values of pulp firmness were observed in pumpkin cultivars when cultivated in both cultivation environments. On the other hand, the moranga and jacarezinho cultivars presented the lowest values. In relation to the longitudinal diameter of the fruits, the sergipana cultivar was larger when cultivated in conventional and alley environments, respectively. On the other hand, cultivars moranga and Jacarezinho presented the lowest values in both cultivation environments. It is verified that for the diameter of the inner cavity of the fruits, the Sergipe cultivar obtained lower values when cultivated in the environment in alleys. When comparing the two cultivation environments, when verifying the fruits of pumpkins cultivated in the conventional environment, the color of the fruits suffered a greater oxidation of vitamins and beta-carotenes, with darker pulp colors in relation to the alley environment, interfering in all three. color luminosity parameters (L *), chromaticity (C *) and hue angle (H °). Given the above, it is necessary to adopt conservation practices for agriculture in order to reduce the harmful effects on the environment. For this, it is recommended to grow pumpkin in an alley environment for greater protection of the environment and the soil.